Pressure-sensitive adhesive for automatic tire labeling and its preparation method
By modifying SIS resin and using a dual-trigger curing mechanism, the problem of tire labeling adhesives being prone to failure in high-temperature environments has been solved, achieving long-term firm adhesion and durability of the labels, and meeting the usage requirements of tires in harsh environments.
Patent Information
- Application Number
- CN202610436468.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-03
- Publication Date
- 2026-06-30
AI Technical Summary
Existing tire labeling adhesives are prone to creep failure under high temperature or harsh environments, and cannot simultaneously meet the requirements of high initial tack, resistance to high vulcanization temperature and resistance to long-term dynamic stress, causing the labels to easily fall off during tire use.
Using maleic anhydride and epoxidized styrene-isoprene-styrene block copolymer (SIS) as the main resin, combined with hydrogenated C9 petroleum resin and terpene phenolic resin as tackifying resins, and adding dicyandiamide latent curing agent, vinyltrimethoxysilane grafted hydrogenated styrene-butadiene block copolymer (SEBS) and nano-reinforcing fillers, a chemically bonded and strongly cross-linked adhesive layer is formed through distributed temperature-controlled mixing and heat-moisture dual-trigger curing mechanism.
It achieves high efficiency and reliability in the tire labeling process, ensuring that the label does not fall off throughout its entire life cycle. It has good environmental adaptability and dynamic durability, and balances processability and high strength, solving the bonding problem of traditional adhesives in extreme environments.
Smart Images

Figure CN122302781A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adhesive technology, specifically to a pressure-sensitive adhesive for automatic tire labeling and its preparation method. Background Technology
[0002] In tire production and logistics, labels need to be quickly and securely affixed to the tire surface. While traditional pressure-sensitive adhesives offer high initial tack and ease of application, their weather resistance, heat resistance, and fatigue resistance are limited. They are prone to creep failure under high temperatures or harsh environments, and labels may detach under repeated tire deformation and centrifugal force. To address this issue, existing technologies primarily improve heat resistance by using physically blended tackifying resins and antioxidants, or by grafting single polar groups to improve initial adhesion. In terms of processing, a one-step high-temperature mixing method is commonly used, and the rheological properties of the adhesive are adjusted to suit coating applications.
[0003] For example, CN121427472A discloses a special hot melt pressure-sensitive adhesive for drip-type coating and its preparation method. The raw materials, by mass, include: 25-35 parts of styrene block copolymer, 40-50 parts of tackifying resin, 20-30 parts of plasticizer, and 0.1-0.5 parts of antioxidant; wherein the styrene block copolymer is preferably S... A compound of 1528, 4411ND, and 6241A is used, with hydrogenated rosin glycerol ester (softening point 85-90℃) preferred as the tackifying resin and medical-grade white oil as the plasticizer. The resulting product exhibits a 180° peel strength >5.0 N / 25 mm, a viscosity of 2000-6500 cps at 180℃, and a dripping accuracy of ±8 μm. It combines excellent adhesion and process adaptability, making it suitable for drip-type coating applications. CN121450295A discloses a power battery insulating pressure-sensitive adhesive and its preparation method. The pressure-sensitive adhesive includes an insulating base material, a fluorine grafting agent, a phosphorus grafting agent, a silicone resin, a crosslinking agent, and a platinum catalyst. The preparation method includes the following steps: S1, fluorine side grafting; S2, phosphorus side grafting; S3, silicone resin dispersion; S4, crosslinking reaction; S5, purification. It utilizes fluorine... Phosphorus side-linking and branching reactions optimize the balance between initial tack and holding tack, constructing a synergistic protective system. Fluorine forms a dense penetration barrier, while phosphorus provides efficient char-forming flame-retardant sites. Combined with the insulating framework of PHMS and the cross-linking network of PHS, this solves the problems of insufficient insulation stability, imbalance between initial tack and holding tack, and poor flame retardancy caused by the lack of targeted functional modification in existing technologies, showing potential for application in the preparation of pressure-sensitive adhesives for power batteries. However, adhesives prepared by existing technologies cannot simultaneously meet the composite requirements of tire labeling for high instantaneous initial tack, resistance to high vulcanization temperatures, and resistance to long-term dynamic stress, and the long-term reliability of the labels under harsh operating environments cannot be guaranteed.
[0004] In summary, how to innovate a new pressure-sensitive adhesive that can combine good environmental adaptability, dynamic durability, and process tolerance, while ensuring that the tire labeling process is efficient and reliable and that the label remains firmly attached throughout the tire's life cycle, is an urgent technical problem to be solved. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a pressure-sensitive adhesive for automatic tire labeling and its preparation method, so as to solve the technical problems of insufficient environmental adaptability, lack of dynamic durability and high sensitivity to process control in the prior art.
[0006] The specific technical solution is as follows:
[0007] A pressure-sensitive adhesive for automatic tire labeling and its preparation method are disclosed. The pressure-sensitive adhesive comprises a base resin, a tackifying resin, and functional components. The base resin is a styrene-isoprene-styrene block copolymer (SIS) modified by maleic anhydride and epoxidation. The tackifying resin is composed of hydrogenated C9 petroleum resin and terpene phenolic resin. The functional components consist of a dicyandiamide latent curing agent, a urea accelerator, a vinyltrimethoxysilane-grafted hydrogenated styrene-butadiene block copolymer masterbatch, nano-reinforcing fillers, and antioxidants. The nano-reinforcing fillers are composed of organically modified montmorillonite premix masterbatch and porous silica microspheres.
[0008] Furthermore, the epoxidized and maleic anhydride-modified styrene-isoprene-styrene block copolymer has an epoxidation degree of 23%~27% and a grafting rate of 1%~3%.
[0009] Furthermore, the porous silica microspheres have an average particle size of 5-20 μm and a particle size of not less than 100 μm. 2 Specific surface area per g.
[0010] A pressure-sensitive adhesive for automatic tire labeling and its preparation method, comprising the following steps: S1: Linear SIS was premixed with maleic anhydride and dicumyl peroxide, and then fed into a twin-screw extruder for melt grafting reaction to obtain SIS-g-MAH melt. The melt was subjected to a high-vacuum devolatilization zone of the extruder at 165℃ and a vacuum of -0.095MPa to remove residual monomers and small molecules. The resulting SIS-g-MAH granules were obtained by underwater pelleting. The SIS-g-MAH granules were dissolved in dichloromethane solvent, and under nitrogen protection at 5℃, m-chloroperoxybenzoic acid was added. The reaction temperature was controlled at ≤10℃ and the mixture was stirred continuously for 4 hours. After the reaction, the mixture was washed sequentially with sodium sulfite aqueous solution and deionized water until neutral, precipitated with methanol, and vacuum dried to obtain dual-modified SIS powder. Organically modified montmorillonite was melt-blended and granulated with the dual-modified SIS granules to prepare an organically modified montmorillonite premix masterbatch for later use.
[0011] S2: The dual-modified SIS granules are put into a mixer for melt plasticization. First, antioxidant 1010 is added and mixed evenly. Then, hydrogenated C9 petroleum resin and terpene phenolic resin are added in sequence and mixed until uniform. Then, the temperature is reduced and organic modified montmorillonite premix masterbatch and porous silica microspheres are added and mixed to achieve nano-intercalation and dispersion. The temperature is further reduced and dicyandiamide latent curing agent, urea accelerator and vinyltrimethoxysilane grafted hydrogenated styrene-butadiene block copolymer (SEBS) masterbatch are added. The mixture is mixed under low temperature and low speed conditions to ensure that each component is uniformly dispersed before discharge to obtain dual-curing hybrid pressure-sensitive adhesive.
[0012] S3: The adhesive material is fed into a hot melt coating machine and coated onto the surface of a corona-treated PET release film. The amount of dry adhesive applied is controlled. Then, it is rapidly cooled to below 40°C by a cooling roller to obtain a single-sided adhesive film with a directional microgroove structure on the surface. The adhesive film is then preheated to 55°C and the release film is peeled off. It is then attached to the side of a green tire by a rubber pressure roller, ensuring that the microgrooves of the adhesive layer face the tire surface to facilitate air venting, thus obtaining a labeled tire blank.
[0013] S4: The labeled tire blank is placed into the vulcanization mold for vulcanization treatment; after vulcanization, the pressure is released and the tire is removed, and post-curing treatment is performed immediately. After the treatment is completed, the tire blank is removed to obtain a permanent label product that has formed a chemical bond with the tire rubber matrix.
[0014] Furthermore, the pressure-sensitive adhesive, based on 100 parts by weight of the double-modified styrene-isoprene-styrene block copolymer, further comprises the following raw material components: 18-28 parts hydrogenated C9 petroleum resin, 5-12 parts terpene phenolic resin, 4-6 parts dicyandiamide latent curing agent, 0.2-0.5 parts urea accelerator, 1-5 parts vinyltrimethoxysilane grafted SEBS masterbatch, 2-3 parts organically modified montmorillonite premix masterbatch, 0.5-1.5 parts porous silica microspheres, and 0.3-0.8 parts antioxidant.
[0015] Furthermore, the melt grafting reaction described in S1 is set to a temperature of 170~180℃, a rotation speed of 180~220rpm, and a time of 3~5 minutes; the vacuum drying is required to be carried out at 45~55℃ for 8~16 hours; and the melt blending is set to a temperature of 145~155℃.
[0016] Further, in step S2, the melting and plasticizing is carried out at a temperature of 130~140℃; then the temperature is reduced to 105~115℃; the temperature is further reduced to 82~88℃; and the mixing is carried out under low temperature and low speed conditions for 2~4 minutes.
[0017] Furthermore, the amount of dry adhesive applied as described in S3 is 45~55 g / m³. 2 The process involves applying the material to the side of a green tire using a rubber roller, with the following bonding conditions: pressure 0.4~0.6MPa, linear speed 12~18m / min, and bonding temperature maintained within the range of 60~70℃.
[0018] Furthermore, the vulcanization treatment described in S4 is set to a temperature of 160~165℃, a steam pressure of 1.2~1.8MPa, and a vulcanization time of 25~35 minutes; the post-curing treatment is set to a temperature of 60~65℃, a relative humidity of 75%~80%, and a curing time of 24~48 hours under forced air circulation.
[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) Achieving chemical bonding and strong crosslinking: The polar reaction sites of the SIS resin modified by maleic anhydride and epoxidation not only enhance the chemical bonding with the polar surface of the tire, but also serve as active sites for subsequent crosslinking, thus simultaneously improving the interfacial bonding strength and the heat resistance of the adhesive layer.
[0020] (2) Balancing processability and high strength: The synergy between silane moisture curing and latent curing agent thermosetting enables sequential crosslinking with heat setting followed by moisture reinforcement. This mechanism ensures that the adhesive layer maintains processability before vulcanization, rapidly builds high strength after vulcanization, and continues to strengthen during long-term service.
[0021] (3) Constructing a heat-resistant and anti-aging barrier: The composite addition of nano-layered silicate and porous silica microspheres systematically improves the thermomechanical properties and environmental stability of the adhesive layer from both the molecular and microstructure dimensions, providing physical protection for long-term durability.
[0022] (4) Ensure bubble-free high-speed labeling: The surface micro-groove structure formed by the coating process creates directional exhaust channels during bonding, which solves the problem of bubble retention in high-speed labeling and achieves a balance between production efficiency and labeling reliability. Attached Figure Description
[0023] Figure 1 This is a flowchart of a pressure-sensitive adhesive for automatic tire labeling and its preparation method according to the present invention.
[0024] Figure 2 The infrared spectrum of the double-modified styrene-isoprene-styrene block copolymer in Example 1 of this invention is shown.
[0025] Figure 3 This is a comparison chart of the experimental results of shear adhesion failure temperature, 180° peel strength, and number of flexures in Experiment Example 1 of this invention. Detailed Implementation
[0026] The following embodiments further explain and illustrate the technical solutions of the present invention. It should be specifically noted that each specific embodiment is a concretization and explanation of the technical solution and should not be considered as a limitation on the scope of protection of the present invention. Those skilled in the art still have the right to modify the technical solutions of these embodiments and make equivalent substitutions for some or all of the technical features, and these modifications or substitutions do not change the essence of the corresponding technical solutions, nor do they cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions described in the present invention.
[0027] This invention proposes a pressure-sensitive adhesive for automatic tire labeling and its preparation method, such as... Figure 1 The diagram shows a flowchart of a pressure-sensitive adhesive for automatic tire labeling and its preparation method, with detailed preparation steps as follows: 1. Synthesis of dual-modified resins and preparation of nano-masterbatches First, styrene-isoprene-styrene block copolymer (SIS) was melt-grafted with maleic anhydride and dicumyl peroxide in a twin-screw extruder at 175°C under nitrogen protection to introduce polar anchoring groups. After devolatilization and granulation, maleic anhydride-grafted SIS granules were obtained. Subsequently, these granules were dissolved in dichloromethane and reacted with m-chloroperoxybenzoic acid at 5°C to precisely introduce epoxy groups as crosslinking active sites onto the carbon-carbon double bonds of the polyisoprene segments. Post-treatment yielded a dual-modified SIS powder with controllable epoxidation degree and grafting rate. Finally, this powder was melt-blended and granulated with organically modified montmorillonite to obtain an organically modified montmorillonite premix masterbatch with a pre-intercalated structure.
[0028] 2. Distributed temperature-controlled active mixing process The process employs a dynamic temperature-controlled intensive mixing technique, specifically: First, at a high temperature of 135℃, the dual-modified SIS resin, hydrogenated C9 petroleum resin, and terpene phenolic resin are fully melted and compatible; then, the temperature is lowered to a medium temperature of 110℃, and organically modified montmorillonite premix masterbatch and porous silica microspheres are added to complete the intercalation dispersion and microstructure construction of the nanofillers; finally, the system is cooled to a safe temperature window below 85℃, and low-speed mixing is used to introduce latent curing agents, accelerators, and silane compounds to ensure the complete survival and uniform distribution of the heat-sensitive components, forming a rubber system that can trigger dual-curing functions.
[0029] 3. Microstructured coating and high-speed bonding The adhesive material is applied through a micro-gravure coating roller with V-shaped grooves of specific dimensions, forming a pressure-sensitive adhesive film with directional air venting channels. After cooling and setting, it is wound up. During labeling, the adhesive film is preheated at 55°C to activate its surface tack. Under a pressure of 0.5MPa and a linear speed of 15m / min, it is precisely pressed onto the tire sidewall by a bonding roller with the temperature controlled at 65°C. The micro-groove structure enables directional air venting during the application process, completely eliminating air bubble defects and meeting the high-speed continuous operation requirements of a fully automated production line.
[0030] 4. Sequential Triggering of Dual Network Solidification After labeling, the tire blank undergoes a vulcanization process at 160-165℃. During this process, the dicyandiamide latent curing agent decomposes upon heating, releasing active groups that rapidly crosslink with the epoxy groups and double bonds of the resin, forming a high-strength initial network. After vulcanization, the tire undergoes programmed post-curing in a forced-cycle environment at 62℃ and 78% relative humidity. This promotes the full hydrolysis and condensation of silane groups, constructing a Si-O-Si secondary crosslinked structure that interpenetrates with the thermosetting network. This sequential curing mechanism ultimately forms a stable interpenetrating polymer network, achieving a durable and reliable chemical bond between the adhesive layer and the tire rubber matrix.
[0031] The technical solution designed by this invention to solve the existing problems includes the following key points: 1. Molecular design of dual-modified SIS base resins Traditional tire labeling pressure-sensitive adhesives mainly rely on solvent-based systems or simple blends of hot melt adhesives. However, these processes often result in weak boundary layers due to interfacial polarity mismatch, leading to unreliable adhesion. This invention proposes a pressure-sensitive adhesive system based on an anchoring-crosslinking dual function. Its core lies in a bifunctionalized SIS base resin, specifically, the SIS is first grafted with maleic anhydride in a molten state, with a grafting rate ranging from 1.8% to 2.2%. A key feature of this sequential design is that the grafting reaction takes place in an anhydrous, acid-free molten environment, ensuring that the maleic anhydride groups are introduced with a complete carboxylic anhydride structure, avoiding potential hydrolysis side reactions in subsequent acidic environments. These carboxylic anhydride groups can generate strong polar interactions with tire rubber, especially at the interface containing silica fillers, and can react with active components in the rubber matrix under vulcanization conditions to form covalent bonds, thereby achieving inherently strong interfacial anchoring. The reason for controlling the grafting rate is that if the grafting rate is too low, there will be insufficient introduced carboxylic anhydride groups, which cannot form a sufficiently dense and strong polar interaction and chemical bond with the tire surface, resulting in insufficient interfacial anchoring force. If the grafting rate is too high, it may damage the microphase separation structure of the SIS matrix, affecting its basic mechanical properties and processing rheology as a thermoplastic elastomer. Excessive anhydride may also interfere with the curing reaction of the epoxy groups. It should be noted that a small number of side reactions are unavoidable during the grafting reaction, such as β-fracture degradation of the SIS backbone or a small amount of crosslinking, resulting in a slight broadening of the molecular weight distribution. Industrial practice shows that under optimized conditions of a grafting rate of 1.8%~2.2%, a reaction temperature of 175℃, and a residence time of 4 minutes, the degree of side reactions can be controlled within an acceptable range and does not affect subsequent processing and the performance of the final product.
[0032] Subsequently, the grafted SIS-g-MAH granules were selectively epoxidized using a low-temperature solution method. m-chloroperoxybenzoic acid (m-CPBA) was used to precisely introduce epoxy groups into the polyisoprene segment, controlling the degree of epoxidation within the range of 23%–27%. The key to this technology lies in the fact that m-CPBA, as a highly selective electrophilic reagent, is well-suited to the reaction environment of the low-temperature solution. Under these conditions, m-CPBA can specifically attack the highly reactive carbon-carbon double bonds on the polyisoprene segment of the SIS molecular chain, while having almost no impact on the styrene hard segments that serve as physical crosslinking points. The low-temperature environment significantly suppresses potential side reactions such as hydrolysis and ring-opening after epoxy group formation, ensuring the purity and functional group integrity of the product. Furthermore, it provides sufficient thermal buffering for the reaction, preventing reagent decomposition or reaction runaway due to localized exothermic reactions, thus achieving precise, quantitative, and localized introduction of epoxy groups into the molecular chain. These epoxy groups not only undergo subsequent thermal crosslinking reactions with latent curing agents, but their inherent increased polarity also directly enhances the cohesive strength of the adhesive. The reason for controlling the epoxidation content within the range of 23% to 27% is that if the epoxidation content is too low, there will be insufficient reaction sites in the resin for crosslinking, which will lead to insufficient network density in the final thermosetting process and a significant decrease in the cohesive strength and heat resistance of the adhesive layer. If the epoxidation content is too high, the polymer chain will be too polar and too rigid, which will not only sacrifice the initial tack and flexibility required by the pressure-sensitive adhesive, but may also cause side reactions due to the excessive density of epoxy groups, affecting storage stability.
[0033] To confirm the successful introduction of bifunctional groups, the obtained bifunctionalized SIS particles were characterized by Fourier transform infrared spectroscopy (FTIR). Figure 2 As shown in the spectrum, at a wavenumber of approximately 825 cm⁻¹ -1 The presence of a distinct epoxy group characteristic absorption peak at approximately 1780 cm⁻¹ confirms the successful introduction of epoxy groups into the polyisoprene segment by the low-temperature solution reaction of m-CPBA. These groups are the active sites for subsequent thermal crosslinking reactions with the dicyandiamide curing agent; simultaneously, at approximately 1780 cm⁻¹... -1 and 1850cm -1 The presence of a distinct bimodal peak, attributed to the symmetric and antisymmetric stretching vibrations of the carbonyl group in the five-membered cyclic anhydride, confirms the success of the melt grafting reaction. These groups will act as strongly polar anchoring sites, responsible for forming physical adsorption or chemical bonding with the tire rubber and silica surfaces. In addition to the characteristic peaks introduced by the modification, the spectrum also contains typical absorption peaks of the SIS base resin: 2850–3000 cm⁻¹. -1 Strong peaks of CH saturated and unsaturated stretching vibrations appeared at 1600 cm⁻¹. -1 and 1450cm -1 The benzene ring skeleton vibration was observed at 699 cm. -1 and 760cm -1 The out-of-plane bending vibration of CH with monosubstituted benzene rings is observed at the location.
[0034] 2. Synergistic effect of distributed temperature-controlled mixing and dual-trigger curing Traditional tire labeling processes typically use pressure-sensitive adhesives that are compounded in a single high-temperature process. This leads to the risk of decomposition or pre-crosslinking of the highly active curing agent during processing. Furthermore, the crosslinked network formed by single heat curing or room temperature curing cannot simultaneously meet the requirements for high-temperature strength, fatigue resistance, and aging resistance. To address this, this invention proposes a synergistic mechanism of distributed temperature-controlled compounding and heat-moisture dual-trigger curing. The principle of this mechanism is as follows: First, through a distributed temperature-controlled compounding process, physical isolation is constructed during processing based on the different thermal stability thresholds of the dicyandiamide latent curing agent, silane compound, and resin matrix. That is, the matrix melting and thickening are completed in the high-temperature range, and then the heat-sensitive component is strictly introduced in the low-temperature range. Thus, the full curing potential is fully preserved through physical blending rather than chemical reaction. In the application phase, the functionalization of the network is achieved through sequential triggering. During tire vulcanization, thermal triggering of dicyandiamide decomposition releases active nitrogen-containing groups that undergo ring-opening addition reactions with the epoxide groups on the epoxide SIS, forming a triazine ring crosslinking structure. Simultaneously, the grafted maleic anhydride groups form ester bonds with the epoxy groups, synergistically constructing a rigid thermosetting main network to provide instantaneous high strength. Subsequently, in a controlled humid heat post-curing environment, moisture triggers the hydrolysis and condensation of silane groups, gradually forming a flexible Si-O-Si secondary interpenetrating network. This network not only further enhances the overall crosslinking density but also significantly improves the dynamic fatigue resistance and long-term durability of the adhesive layer due to its dynamic characteristics.
[0035] Example 1 Table 1 Raw Material Information Table
[0036] A pressure-sensitive adhesive for automatic tire labeling and its preparation method, comprising the following steps: S1: 100 parts of linear styrene-isoprene-styrene block copolymer, 2 parts of maleic anhydride, and 0.3 parts of dicumyl peroxide were premixed for 3 minutes at room temperature in a high-speed mixer to ensure uniform dispersion of the components. The premix was fed into a twin-screw extruder and subjected to a melt grafting reaction at 175°C and 200 rpm for 4 minutes under nitrogen protection to obtain SIS-g-MAH melt. The melt was then fed into the high-vacuum devolatilization zone of the extruder to remove residual monomers and small molecules at 165°C and a vacuum of -0.095 MPa. The resulting pellets were then granulated underwater to obtain SIS-g-MAH granules. 100 parts of SIS-g-MAH granules were dissolved in 200 parts of dichloromethane solvent. Under nitrogen protection at 5°C, 7.2 parts of m-chloroperoxybenzoic acid were added, and the reaction was continuously stirred for 4 hours while maintaining a reaction temperature ≤10°C. After the reaction, the mixture was washed sequentially with 10% sodium sulfite aqueous solution and deionized water until neutral, precipitated with methanol, and then vacuum dried at 50°C for 12 hours under a vacuum of -0.095 MPa to obtain dual-modified SIS powder. 20 parts of organically modified montmorillonite and 30 parts of dual-modified SIS powder were melt-blended and granulated in a twin-screw extruder at 150°C to prepare an organically modified montmorillonite premix masterbatch for later use.
[0037] S2: 60 parts of dual-modified SIS granules were put into a mixer and melted and plasticized for 3 minutes at 135°C and 60 rpm. First, 0.5 parts of antioxidant 1010 were added and mixed. Then, 22 parts of hydrogenated C9 petroleum resin and 8 parts of terpene phenolic resin were added and mixed for 5 minutes until uniform. Then, the temperature was lowered to 110°C and 2.5 parts of organic modified montmorillonite premix masterbatch and 1 part of porous silica microspheres were added and mixed for 5 minutes to achieve nano-intercalation and dispersion. The temperature was further lowered to 85°C and 5 parts of dicyandiamide powder, 0.3 parts of urea accelerator, and 3 parts of vinyltrimethoxysilane grafted SEBS masterbatch were added. The mixture was mixed at a low temperature of 30 rpm for 3 minutes to ensure that the components were uniformly dispersed before discharge to obtain dual-curing hybrid pressure-sensitive adhesive.
[0038] S3: The obtained adhesive is fed into a hot melt coating machine. After being metered by a gear pump, it is applied to the corona-treated PET release film surface at a speed of 18 m / min through a micro-gravure coating roller with longitudinal V-shaped grooves engraved on its surface. The dry adhesive quantity is controlled at 50 g / m³. 2 The film is rapidly cooled to below 40°C by a cooling roller to obtain a single-sided adhesive film with a directional microgroove structure on its surface. The film is then preheated to 55°C and the release film is peeled off. It is then bonded to the side of a green tire by a rubber pressure roller at a pressure of 0.5MPa and a linear speed of 15m / min. The bonding temperature is maintained at 65°C to ensure that the microgrooves of the adhesive layer face the tire surface to facilitate air venting, resulting in a labeled tire blank.
[0039] S4: The labeled tire blank is loaded into the vulcanization mold and vulcanized for 30 minutes in a flat vulcanizing machine at 162°C and 1.5MPa steam pressure. During this process, dicyandiamide undergoes a ring-opening addition reaction with epoxy groups under the action of urea accelerators to form a triazine ring crosslinking structure. At the same time, the anhydride groups of SIS-g-MAH form ester bonds with epoxy groups, synergistically constructing a thermosetting main network. After vulcanization, the pressure is released and the tire is removed. After natural cooling to below 80°C, it is immediately transferred to a post-curing chamber and cured for 36 hours at 62°C, 78% relative humidity, and forced air circulation. This allows the silane groups to fully hydrolyze and condense to form a Si-O-Si crosslinking network, ultimately constructing a heat-moisture dual-curing interpenetrating network structure, resulting in a permanent labeled product that is chemically bonded to the tire rubber matrix.
[0040] Example 2 The preparation method is the same as in Example 1, except that: S1: The melt grafting reaction at 175℃ and 200 rpm for 4 minutes was replaced with a melt grafting reaction at 170℃ and 180 rpm for 3 minutes; 200 parts of dichloromethane solvent was replaced with 150 parts of dichloromethane solvent; 7.2 parts of m-chloroperoxybenzoic acid was replaced with 6.5 parts of m-chloroperoxybenzoic acid; vacuum drying at 50℃ for 12 hours was replaced with vacuum drying at 45℃ for 8 hours; melt blending at 150℃ was replaced with melt blending at 145℃. S2: Replace 60 parts of dual-modified SIS granules with 50 parts of dual-modified SIS granules; replace 135℃ with 130℃; replace adding 0.5 parts of antioxidant 1010 first with adding 0.3 parts of antioxidant 1010 first; replace 22 parts of hydrogenated C9 petroleum resin and 8 parts of terpene phenolic resin with 18 parts of hydrogenated C9 petroleum resin and 5 parts of terpene phenolic resin; lower the temperature to 110℃, add 2.5 parts of organically modified montmorillonite premix masterbatch and 1 part of porous silica microspheres. Instead of lowering the temperature to 105℃ and adding 2 parts of organically modified montmorillonite premix masterbatch and 0.5 parts of porous silica microspheres; and continuing to lower the temperature to 85℃ and adding 5 parts of dicyandiamide powder, 0.3 parts of urea accelerator, and 3 parts of vinyltrimethoxysilane-grafted SEBS masterbatch, continue to lower the temperature to 82℃ and add 4 parts of dicyandiamide powder, 0.2 parts of urea accelerator, and 1 part of vinyltrimethoxysilane-grafted SEBS masterbatch; and instead of low-temperature mixing for 3 minutes, mix for 2 minutes. S3: The amount of dry adhesive applied should be controlled at 50g / m². 2 Replace with dry adhesive with a quantity control of 45g / m³ 2 The bonding process was changed from using 0.5MPa pressure and 15m / min linear speed to using 0.4MPa pressure and 12m / min linear speed; the bonding temperature was changed from being maintained at 65℃ to being maintained at 60℃. S4: Vulcanizing for 30 minutes at 162℃ and 1.5MPa steam pressure on a flat vulcanizing machine is replaced with vulcanizing for 25 minutes at 160℃ and 1.2MPa steam pressure on a flat vulcanizing machine; and curing for 36 hours at 62℃, 78% relative humidity, and forced air circulation is replaced with curing for 24 hours at 60℃, 75% relative humidity, and forced air circulation. All other steps are the same.
[0041] Example 3 The preparation method is the same as in Example 1, except that: S1: The melt grafting reaction at 175℃ and 200 rpm for 4 minutes was replaced with a melt grafting reaction at 180℃ and 220 rpm for 5 minutes; 200 parts of dichloromethane solvent was replaced with 250 parts of dichloromethane solvent; 7.2 parts of m-chloroperoxybenzoic acid was replaced with 8.0 parts of m-chloroperoxybenzoic acid; vacuum drying at 50℃ for 12 hours was replaced with vacuum drying at 55℃ for 16 hours; melt blending at 150℃ was replaced with melt blending at 155℃. S2: Replace 60 parts of dual-modified SIS granules with 70 parts of dual-modified SIS granules; replace 135℃ with 140℃; replace adding 0.5 parts of antioxidant 1010 with adding 0.8 parts of antioxidant 1010 first; replace 22 parts of hydrogenated C9 petroleum resin and 8 parts of terpene phenolic resin with 28 parts of hydrogenated C9 petroleum resin and 12 parts of terpene phenolic resin; lower the temperature to 110℃, add 2.5 parts of organically modified montmorillonite premix masterbatch and 1 part of porous silica microspheres. Instead of lowering the temperature to 115℃ and adding 3 parts of organically modified montmorillonite premix masterbatch and 1.5 parts of porous silica microspheres; and continuing to lower the temperature to 85℃ and adding 5 parts of dicyandiamide powder, 0.3 parts of urea accelerator, and 3 parts of vinyltrimethoxysilane-grafted SEBS masterbatch, continue to lower the temperature to 88℃ and add 6 parts of dicyandiamide powder, 0.5 parts of urea accelerator, and 5 parts of vinyltrimethoxysilane-grafted SEBS masterbatch; and instead of low-temperature mixing for 3 minutes, mix for 4 minutes. S3: The amount of dry adhesive applied should be controlled at 50g / m². 2 Replace with dry adhesive with a quantity control of 55 g / m³ 2 The bonding pressure of 0.5MPa and linear speed of 15m / min was replaced with the bonding pressure of 0.6MPa and linear speed of 18m / min; the bonding temperature of 65℃ was replaced with the bonding temperature of 70℃. S4: Vulcanizing for 30 minutes at 162℃ and 1.5MPa steam pressure on a flat vulcanizing machine is replaced with vulcanizing for 35 minutes at 165℃ and 1.8MPa steam pressure on a flat vulcanizing machine; and curing for 36 hours at 62℃, 78% relative humidity, and forced air circulation is replaced with curing for 48 hours at 65℃, 80% relative humidity, and forced air circulation. All other steps are the same.
[0042] Comparative Example 1 Pressure-sensitive adhesive was prepared using a traditional hot-melt pressure-sensitive adhesive general formulation and a one-step mixing process. The specific preparation method was as follows: 100 parts of unmodified SIS, 25 parts of hydrogenated C9 petroleum resin, 10 parts of terpene resin, 2 parts of antioxidant 264, 40 parts of naphthenic oil and 15 parts of calcium carbonate were put into an internal mixer at 150°C and 60 rpm for 20 minutes until homogeneous. After discharge, the mixture was coated and laminated under the same conditions and vulcanized at 162°C to obtain a control sample.
[0043] Comparative Example 2 The preparation method is the same as in Example 1, except that: S1: Replace 100 parts of linear styrene-isoprene-styrene block copolymer with 100 parts of unmodified styrene-isoprene-styrene block copolymer; All other steps are the same.
[0044] Comparative Example 3 The preparation method is the same as in Example 1, except that: S3: Replace the micro-gravure coating roller with longitudinal V-shaped grooves on the surface with a smooth micro-gravure coating roller. All other steps are the same.
[0045] Comparative Example 4 The preparation method is the same as in Example 1, except that: S3: The steps of adding 5 parts dicyandiamide powder and 0.3 parts urea accelerator are omitted; All other steps are the same.
[0046] Experimental Example 1 The permanent labeling products prepared in Examples 1-3 and Comparative Examples 1-4 were tested: (1) Shear adhesion failure temperature: Referring to GB / T 4851-2014 "Test Method for Holding Strength of Pressure-Sensitive Adhesive Tapes", the test piece with adhesive tape was vertically suspended on the holding strength tester, and a standard weight of 1 kg was applied in the lower basket. Then, the entire device was placed in a programmable temperature oven and heated from room temperature at a constant rate. The temperature at which the test piece failed due to shear failure was continuously monitored by the instrument and recorded. This temperature is the shear adhesion failure temperature. To obtain reliable data, at least 5 parallel samples were tested in each group, and the average value of the results was taken.
[0047] (2) 180° Peel Strength: Referring to GB / T 2792-2014 "Test Method for 180° Peel Strength of Pressure-Sensitive Adhesive Tapes", a 25mm wide tape sample is pressed against a standard roller with a mass of 2000g±50g at a constant speed for a specified number of times to make it flatly adhered to a standard stainless steel plate or actual tire rubber sheet. After standing for a specified time in a standard laboratory environment, the unbonded end is folded 180° in the opposite direction and clamped in the upper clamp of a universal testing machine, while the substrate is clamped in the lower clamp. The testing machine peels at a constant rate of 300mm / min, automatically records the force curve during the peeling process, and takes the average force value of the effective stroke in the middle to calculate the peel strength per unit width. At least 5 samples should be tested in each group, and the average value of the results is taken.
[0048] (3) Number of flexural cycles: Referring to ASTM D813, "Standard Test Method for Deterioration of Rubber—Crack Propagation", a specimen is made by sandwiching two pieces of rubber with an adhesive layer. The bonded specimen must be mounted on a flexural testing machine, with the adhesive layer located at the center of the flexural curve. The testing machine uses a crank-connecting rod mechanism to produce a constant reciprocating flexural deformation of the specimen within a set stroke. The number of flexural cycles experienced by the specimen during repeated flexing until a crack of a specified length appears in the rubber layer is recorded using a counter. At least 5 specimens should be tested in each group, and the average value of the results should be taken.
[0049] Experimental Example 2 The double-modified SIS granules prepared in step S1 of Example 1 were characterized by Fourier transform infrared spectroscopy (FTIR): (1) Sampling: Approximately 5g of sample was randomly selected from the prepared double-modified SIS granules. The granules had undergone high-vacuum devolatilization treatment in a twin-screw extruder to remove residual monomers and small molecules, making them relatively pure.
[0050] (2) Sample preparation: Take a small amount of granules and hot press them at 120°C on a flat vulcanizing machine to form a transparent film with a thickness of about 0.1 mm.
[0051] (3) Background acquisition: Before placing the sample, the background spectrum of the empty optical path is acquired to subtract the influence of the ambient air.
[0052] (4) Sample scanning: The infrared spectral data of the sample is collected and the baseline is automatically corrected and smoothed by the software to obtain the final transmittance spectrum.
[0053] Table 2 Comparison of experimental results of Examples 1-3 and Comparative Examples 1-4
[0054] The experimental results of Examples 1-3 and Comparative Examples 1-4 are shown in Table 2 and Figure 3 As shown, the permanent labeling product obtained by the present invention fully meets the requirements of tire labeling in terms of performance. At the same time, in terms of process, its parameters are located in the most stable and controllable industrialization window, and a balance between excellent performance and optimal cost structure is achieved. Therefore, it is established as the best implementation point of the present invention.
[0055] Example 2, by reducing the reaction intensity and decreasing the amounts of the main component, tackifying resin, and curing agent, resulted in a systematic decrease in heat resistance, peel strength, and fatigue resistance. This directly demonstrates that within the technical framework of this invention, there is a clear quantitative positive correlation between the final performance and the amount and degree of modification of key components. Example 3, by enhancing the reaction intensity and increasing the amounts of the main component, tackifying resin, and curing agent, achieved the upper limits of heat resistance, peel strength, and fatigue resistance. This further confirms the positive correlation between performance and key parameters. However, this approach is not the optimal implementation point because it significantly increases raw material costs and process energy consumption in order to achieve the ultimate performance.
[0056] Comparative Examples 1-4, lacking key technologies, showed varying degrees of reduced overall performance compared to the original examples. Comparative Example 1 employed a conventional hot-melt pressure-sensitive adhesive formulation and a one-step mixing process. Because this formulation lacked chemically modified resin and a reactive curing system, its final product relied entirely on physical adhesion and cooling for setting, resulting in significantly lower shear adhesion failure temperature and 180° peel strength compared to the present invention, as well as severely deteriorated dynamic flexural life. These results demonstrate that without the bifunctional resin design and dual-curing mechanism provided by the present invention, traditional formulations and processes alone cannot meet the requirements for heat resistance, strength, and durability in tire labeling. Comparative Example 2, using completely unmodified SIS resin, exhibited the worst heat resistance, peel strength, and dynamic flexural life among all comparisons. This directly proves that the lack of chemical modification of SIS, especially the polar anchoring groups provided by MAH grafting, will prevent the adhesive from forming effective chemical bonds and strong interfacial interactions with the tire rubber surface, which is the root cause of the failure of the entire bonding system. Comparative Example 3, due to the use of a smooth surface coating and the absence of directional venting microgroove structures, showed a significant increase in bubble rate and a decrease in bonding yield during high-speed automatic labeling. This result proves that even with excellent chemical adhesion and bulk strength, the problem of bubble defects in production cannot be solved without a microstructure design that matches the high-speed automated labeling process, verifying the indispensability of surface microgroove structures for achieving high-efficiency and high-reliability automatic labeling. Comparative Example 4, due to the lack of latent curing agents and accelerators, showed significantly insufficient initial peel strength and dynamic flexural life after vulcanization. This result proves that moisture curing alone cannot provide sufficient structural strength immediately after tire vulcanization, verifying the decisive role of the thermal triggering network in the heat-moisture dual-trigger curing mechanism in constructing an initial high-strength skeleton and ensuring reliable adhesion of the finished product.
[0057] In summary, this invention, through a stepwise temperature-controlled mixing process using a bifunctional modified SIS resin, fully protects the activity of the heat-sensitive curing components. Ultimately, during the vulcanization and post-curing processes of the tire, sequentially triggering thermal crosslinking and moisture crosslinking, a strong and tough interpenetrating network structure is constructed. This series of interconnected processes ultimately solves the key challenge of pressure-sensitive adhesives in automatic tire labeling—the inability to simultaneously achieve high-speed labeling, withstand high-temperature vulcanization, and meet the requirements of long-term dynamic use.
Claims
1. A pressure-sensitive adhesive for automatic tire labeling, comprising a base resin, a tackifying resin, and functional components, characterized in that, The main resin is a styrene-isoprene-styrene block copolymer modified by maleic anhydride and epoxidation; the tackifying resin is composed of hydrogenated C9 petroleum resin and terpene phenolic resin; the functional components are composed of dicyandiamide latent curing agent, urea accelerator, vinyltrimethoxysilane-grafted hydrogenated styrene-butadiene block copolymer masterbatch, nano-reinforcing filler, and antioxidant; the nano-reinforcing filler is composed of organically modified montmorillonite premix masterbatch and porous silica microspheres.
2. The pressure-sensitive adhesive for automatic tire labeling as described in claim 1, characterized in that, The pressure-sensitive adhesive, based on 100 parts by weight of the double-modified styrene-isoprene-styrene block copolymer, further comprises the following raw material components: 18-28 parts hydrogenated C9 petroleum resin, 5-12 parts terpene phenolic resin, 4-6 parts dicyandiamide latent curing agent, 0.2-0.5 parts urea accelerator, 1-5 parts vinyltrimethoxysilane grafted hydrogenated styrene-butadiene block copolymer masterbatch, 2-3 parts organically modified montmorillonite premix masterbatch, 0.5-1.5 parts porous silica microspheres, and 0.3-0.8 parts antioxidant.
3. The pressure-sensitive adhesive for automatic tire labeling as described in claim 1, characterized in that, The styrene-isoprene-styrene block copolymer modified by maleic anhydride and epoxidation has an epoxidation degree of 23%~27% and a grafting rate of 1%~3%.
4. The pressure-sensitive adhesive for automatic tire labeling as described in claim 1, characterized in that, The porous silica microspheres have an average particle size of 5-20 μm and a particle size of not less than 100 μm. 2 Specific surface area per g.
5. The pressure-sensitive adhesive for automatic tire labeling as described in claim 1, characterized in that, The pressure-sensitive adhesive has a shear adhesion failure temperature ≥150℃, a 180° peel strength ≥20N / 25mm, and a flexural cycle ≥100,000 times.
6. A method for preparing a pressure-sensitive adhesive for automatic tire labeling as described in any one of claims 1 to 5, characterized in that, Specifically, the steps include the following: S1: A linear styrene-isoprene-styrene block copolymer is premixed with maleic anhydride and dicumyl peroxide, and then subjected to a melt grafting reaction to obtain a maleic anhydride-grafted styrene-isoprene-styrene block copolymer melt. The melt is then introduced into a high-vacuum devolatilization zone, where residual monomers and small molecules are removed at 165°C and a vacuum of -0.095 MPa. The resulting material is then granulated underwater to obtain maleic anhydride-grafted styrene-isoprene-styrene block copolymer pellets. The pellets are dissolved in dichloromethane. In a solvent, m-chloroperoxybenzoic acid was added at 5°C under nitrogen protection, and the reaction temperature was controlled at ≤10°C with continuous stirring for 4 hours. After the reaction was completed, the mixture was washed with sodium sulfite aqueous solution and deionized water until neutral, precipitated with methanol and dried under vacuum to obtain bis-modified styrene-isoprene-styrene block copolymer granules. Organically modified montmorillonite and bis-modified styrene-isoprene-styrene block copolymer granules were melt-blended and granulated to prepare organically modified montmorillonite premixed masterbatch for later use. S2: The granules of the dual-modified styrene-isoprene-styrene block copolymer are melt-plasticized. First, an antioxidant is added and mixed evenly. Then, hydrogenated C9 petroleum resin and terpene phenolic resin are added sequentially and mixed until uniform. Then, the temperature is lowered and organic modified montmorillonite premix masterbatch and porous silica microspheres are added and mixed to achieve nano-intercalation and dispersion. The temperature is further lowered and dicyandiamide latent curing agent, urea accelerator and vinyltrimethoxysilane grafted hydrogenated styrene-butadiene block copolymer masterbatch are added. The mixture is mixed under low temperature and low speed conditions to ensure that each component is uniformly dispersed before discharge to obtain the dual-curing hybrid pressure-sensitive adhesive. S3: Apply the dual-curing hybrid pressure-sensitive adhesive to the surface of the corona-treated PET release film, control the amount of dry adhesive applied, and then quickly cool it to below 40°C to obtain a single-sided adhesive film; then preheat the adhesive film to 55°C and peel off the release film, attach it to the side of the green tire to obtain a tire blank with a label. S4: Vulcanize the labeled tire blanks; After vulcanization, the pressure is released and the tire is removed. Immediately afterward, a post-curing treatment is performed. Once the treatment is complete, the tire is removed, resulting in a permanent label product that has formed a chemical bond with the tire rubber matrix.
7. The method for preparing a pressure-sensitive adhesive for automatic tire labeling as described in claim 6, characterized in that, The melt grafting reaction described in S1 is performed under the following conditions: temperature 170-180℃, rotation speed 180-220rpm, and time 3-5 minutes; the vacuum drying is performed at 45-55℃ for 8-16 hours; and the melt blending is performed at a temperature of 145-155℃.
8. The method for preparing a pressure-sensitive adhesive for automatic tire labeling as described in claim 6, characterized in that, S2 describes the melting and plasticizing process at a temperature of 130-140°C; the temperature is then reduced to 105-115°C; the temperature is further reduced to 82-88°C; and the mixture is then kneaded at a low temperature and low speed for 2-4 minutes.
9. The method for preparing a pressure-sensitive adhesive for automatic tire labeling as described in claim 6, characterized in that, The amount of dry adhesive applied as described in S3 is 45~55 g / m³. 2 The bonding condition for the green tire sidewall is set as follows: pressure 0.4~0.6MPa, linear speed 12~18m / min, and bonding temperature maintained within the range of 60~70℃.
10. The method for preparing a pressure-sensitive adhesive for automatic tire labeling as described in claim 6, characterized in that, The vulcanization treatment described in S4 is set to a temperature of 160~165℃, a steam pressure of 1.2~1.8MPa, and a vulcanization time of 25~35 minutes; the post-curing treatment is set to a temperature of 60~65℃, a relative humidity of 75%~80%, and a curing time of 24~48 hours under forced air circulation.
Citation Information
Patent Citations
Special hot-melt pressure-sensitive adhesive for instillation type coating and preparation method of special hot-melt pressure-sensitive adhesive
CN121427472A
Power battery insulation pressure-sensitive adhesive and preparation method thereof
CN121450295A
